Seniors and Information Technology in China. Issue 2 (1st February 2016) - Chen, Alexander N.; Downey, James P.; McGaughey, Ronald E.; Jin, Kan
Abstract : Technology, particularly information technology (IT), is changing rapidly and offers many advantages for users. IT has the potential to improve one's quality of life, but only if used. Research has shown that, in most developed and developing nations, senior use of IT lags behind that of other segments of society. This "gray divide" is a concern for government, business, and others. Concern about senior adoption and use of IT has been the motivation for numerous studies and is the motivation for this study of Chinese seniors. This exploratory study examines urban Chinese seniors' IT use, computers and mobile phones in particular, but also their attitudes and behaviors as they relate to the use of those devices. More specifically it examines several potential factors that motivate or hinder senior's use of information technology, including self-efficacy, satisfaction, comfort with technology, and both positive and negative attitudes. This study provides some insight into the quantity and diversity of Chinese senior technology use in urban China. Particularly noteworthy, the study found that technology ownership was quite high, and in general the Chinese seniors studied had positive attitudes and beliefs concerning information technology. This is generally good news for the Chinese government, which must efficiently provide services for the growing population of Chinese seniors, as well as for businesses that wish to capitalize on one of the largest senior populations in the world.